2016
DOI: 10.21037/jtd.2016.07.63
|View full text |Cite
|
Sign up to set email alerts
|

Insights into ascending aortic aneurysm pathogenesis using in vivo and ex vivo imaging systems in angiotensin II-infused mice

Abstract: Insights into ascending aortic aneurysm pathogenesis using in vivo and ex vivo imaging systems in angiotensin II-infused mice. J Thorac Dis 2016;8(8):E822-E824.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…13 About the same time, it was also shown that systemic neutralization of TGF-β (transforming growth factor beta) activity exacerbated thoracic aortic disease in Ang IIinfused wild-type mice. 36 Although precise roles for the renin-angiotensin system and TGF-β remain unclear in the context of TAADs, [37][38][39] chronic Ang II infusion remains a convenient and reproducible model for studying potential mechanisms and time courses of particular thoracic aortopathies 22 even though direct translation to human pathology is limited. Indeed, lesions typically arise rapidly in the same anatomic location, within 3 to 5 days of Ang II infusion, and independent of hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 About the same time, it was also shown that systemic neutralization of TGF-β (transforming growth factor beta) activity exacerbated thoracic aortic disease in Ang IIinfused wild-type mice. 36 Although precise roles for the renin-angiotensin system and TGF-β remain unclear in the context of TAADs, [37][38][39] chronic Ang II infusion remains a convenient and reproducible model for studying potential mechanisms and time courses of particular thoracic aortopathies 22 even though direct translation to human pathology is limited. Indeed, lesions typically arise rapidly in the same anatomic location, within 3 to 5 days of Ang II infusion, and independent of hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the geometric complexity of Ang II-induced lesions, advanced imaging and methods of quantification are needed to delineate the observed intramural and regional variations in remodeling. 22 In this article, we combine ex vivo a custom panoramic digital image correlation (pDIC) approach with optical coherence tomography (OCT) imaging and biaxial biomechanical testing to quantify evolving local microstructural composition, mural degeneration, and mechanical properties of the ascending aorta as a function of the duration of Ang II infusion. Despite using a standard genetically inbred hyperlipidemic mouse strain-Apoe −/− on a C57BL/6J background-we found that the extent of mural defects and the degree of aortic dilatation varied considerably from mouse to mouse, consistent with prior studies focused on remodeling over a set duration of Ang II infusion.…”
mentioning
confidence: 99%
See 1 more Smart Citation